The rise. 1970 - Castrovilla, Selene, 1966- (New York : Franklin Watts, an imprint of Scholastic Inc., 2023)
Explores the key events of the Civil Rights Movement, focusing on the year 1970, including Charles Edward Gordone who became the first African American playwright to win the Pulitzer Prize, Essence magazine, and more.
Introduction: the way it was -- A divided moment -- The whole world was watching -- Women catch a second wave -- Protests -- Race riots -- Searching for fairness -- Conclusion: the legacy of 1970 in civil rights history -- Biography: Aileen Hernandez -- Timeline.
School Library Journal, April 2023
Booklist, April 2023
Includes bibliographical references (page 92) and index.
8.9
5-8
1160L
Keywords: African Americans -- Civil rights -- History -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights workers -- United States -- Juvenile literature; African Americans -- Civil rights -- History; Civil rights movements -- History -- 20th century; Civil rights workers